Swedish Party Membership Survey 2019, prepared dataset - Kölln, Ann-Kristin; Polk, Jonathan (University of Gothenburg, 2024)
In 2018, representatives from all the Swedish parliamentary parties (plus the Feminist Initiative) agreed to participate in and conduct an online survey among their party members. The questions are similar to those asked in the Swedish party membership survey in 2015. The survey was administered by the Laboratory of Opinion Research (LORE) at the University of Gothenburg.
At the end of the field period at the beginning of May 2019, a total of 20,605 party members had responded. The response rate varies between 9.4 percent (Feminist Initiative) and 29.9 percent (Christian Democrats).

In spring 2022, the data file for SPMS 2019 was reworked to enable better possibilities of sharing data upon request. This entailed the recoding of two variables (year of birth and year of entry into the party), as well as the removal of all variables and response alternatives with free text fields and postcodes. Below is a list of recoded or deleted variables. Further information can be found in the enclosed code books. The complete dataset is available with restricted access.

Recoded variables: yearmember; yearofbirth
Removed variables: Q32_2_text; Q33_2_text; Q112; Q110_6_text; postcode_clean
Added variables: county, uncertain_county

The data is available as a STATA dataset (.dta) as well as coded comma-separated values (.csv).

Under 2018 tackade representanter från alla de svenska riksdagspartierna (plus Feministiskt Initiativ) ja till att vara med och genomföra en nätbaserad enkät bland sina partimedlemmar. Frågorna liknar de som ställdes i svenska partimedlemsundersökningen 2015. Undersökningen administrerades av Laboratory of Opinion Research (LORE) vid Göteborgs universitet.
Vid slutet av fältperioden i början av maj 2019 hade totalt 20.605 partimedlemmar svarat. Svarsfrekvensen varierar mellan 9,4 procent (Feministiskt Initiativ) och 29,9 procent (Kristdemokraterna).

Under våren 2022 omarbetades datafilen för SPMS 2019 för att öka möjligheterna för tillgängliggörande av data i en utlämningsprocess. Detta innebar omkodning av två variabler (födelseår och år för inträde i partiet), samt borttagning av samtliga variabler och svarsalternativ med fritextfält och postkoder. Nedan återfinns en lista över omkodade eller borttagna variabler. Ytterligare information finns i bifogade kodböcker. Det fullständiga datasetet finns att tillgå med begränsad tillgång.

Omkodade variabler: yearmember; yearofbirth
Borttagna variabler: Q32_2_text; Q33_2_text; Q112; Q110_6_text; postcode_clean
Tillagda variabler: county, uncertain_county

Datasetet finns tillgängligt i STATA-format (.dta) och som kodade kommaseparerade värden (.csv).
Svenska partimedlemsundersökningen 2019, bearbetat dataset
Keywords: POLITICS; POLITIK; MEMBERSHIP; MEDLEMSKAP; DEMOCRACY; DEMOKRATI; PARTY POLITICS; PARTIPOLITIK; POLITICAL PARTIES; POLITISKA PARTIER; Political behaviour and attitudes; Politiska beteenden och attityder; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)